Supporting Factors for Implementing Project-Based Teaching Factory Learning in Wood and Rattan Craft Workshops - Faridah Nur Amalina; Anis, Samsudin; Na’am, Fakhrihun (Universitas Negeri Semarang, 2023)
This study aims to determine and analyze the implementation of the Teaching Factory learning program and analyze the implementation of the Teaching Factory learning based on the production unit of the Creative Wood and Rattan Craft Expertise Program at SMK Negeri 9 Surakarta. The research method used a qualitative descriptive approach with a case study research design. This method is suitable for the issue we investigated regarding the implementation of project-based Teaching Factory learning in wood and rattan craft workshops. In the planning phase of Teaching Factory learning, the research results are explained related to the implementation process as the basis for implementing Teaching Factory learning implementation in schools, namely supporting policies divided into central policies, and school policies. The implementation of Teaching Factory learning is conducted through document studies and interviews. The determination of the produced products aligns with the stages of developing the Teaching Factory model 4, which are products/services that are correct, neat, have marketability, meet societal demands, and can be mass-produced by teams. Implementation aspects ranging from planning, implementation and evaluation are highly dependent on learning implementation activities in which there are main elements of students who are active, creative and can work together.